Seeking and Sharing Health Information Online: Comparing Search Engines and Social Media - De Choudhury, Munmun; Morris, Meredith Ringel; White, Ryen W. (Proceedings of CHI 2014, 2014)
Search engines and social media are two of the most commonly used online services; in this paper, we examine how users appropriate these platforms for online health activities via both large-scale log analysis and a survey of 210 people. While users often turn to search engines to learn about serious or highly stigmatic conditions, a surprising amount of sensitive health information is also sought and shared via social media, in our case the public social plat-form Twitter. We contrast what health content people seek via search engines vs. share on social media, as well as why they choose a particular platform for online health activities. We reflect on the implications of our results for designing search engines, social media, and social search tools that better support people’s health information seeking and sharing needs.